Incidental and Multimodal High Variability Phonetic Training: Potential, Limits, and Future Directions. Issue 4 (27th May 2022) - Saito, Kazuya; Hanzawa, Keiko; Petrova, Katya; Kachlicka, Magdalena; Suzukida, Yui; Tierney, Adam
Abstract: Scholars have extensively investigated the effectiveness of high variability phonetic training (HVPT), that is, identification and discrimination of second language speech sounds produced by multiple speakers followed by trial‐by‐trial feedback. Building on the notion of incidental and multimodal learning in cognitive psychology (e.g., Lim & Holt, 2011), we developed a new, HVPT‐based videogame paradigm in which participants aimed to shoot clay targets as fast as possible while being guided to learn sound cues as a by‐product of planned learning. Focusing on the speech acquisition of 58 Japanese English‐as‐a‐foreign‐language learners, the current study set out to test the pedagogical potential and limits of the incidental HVPT approach. According to the results of statistical analyses, the effectiveness of incidental HVPT can be more clearly observed if it focuses on more learnable targets (e.g., acquisition of English [æ]–[ʌ] rather than [r]–[l] contrasts) with gains being more generalizable from trained to new speakers' voices and from perception to production dimensions. Abstract :